PENGARUH PIUTANG DAN PERSEDIAAN TERHADAP PROFITABLITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Daulay, Siti Aisyah Br.; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the Effect of Account Receivable and Inventory Against Profitability on Manufacturing Company Listed in Indonesia Stock Exchange. Independent variables using accounts receivables turnover, receivables collection period, inventory turnover and the average days of inventory, while the dependent variable using financial ratios profitability of the Net Profit Margin (NPM). The method used to observe the effect of account receivable and inventory against profitability is by using multiple linear regression.Data used in this research is secondary data, financial reports (annual report). As for the data manufacturing company listed on the IDX for 5 years from 2009 to 2013. Sampling was done by purposive sampling, as for the sample is 4 manufacturing company sectore food and drink . Classic assumption test in this study include normality test, multikoliniearitas, heterocedasticity test, autocorrelation test. Analysis data using multiple linear regression analysis, f test, and coefficient of determination test. Analysis data using multiple linear regression analysis with SPSS 17.The results of this research simultaneously (f test) showed a significant effect of the account receibable and inventory variables againts profitability on manufacturing company listed in the Indonesia Stock Exchange (IDX).Keywords: Accounts Receivables Turnover, Receivables Collection Period, Inventory Turnover and The Average Days Of Inventory, Net Profit Margin.